Brains boxed in. (Economist, 2007)
The article reports on eastern Europe's software industry boom. Foreign firms are surging into Romania and the Ukraine, attracted by cheap, skilled, multilingual computer programmers. But with their salaries rising, Romanian programmers may soon be unaffordable for Western firms. As a result, one Bulgarian firm can't afford local employees anymore, and is outsourcing to Vietnam. Some advocates say that public-private partnerships in education will help increase programming capacity.